The development of guidelines to improve the interpersonal communication of students in preparation for entering the workforce thought information services - Fitri Yunizar; A. Muri Yusuf; Yarmis Syukur (International Journal of Applied Counseling and Social Sciences, 2020)
Communication is very important in the world of work. With communication, individuals can socialize with other individuals well. But in reality, there are still many individuals who have not been able to communicate well. Vocational High School (SMK) is a secondary education that prepares students to become professional workers. Therefore, it is expected that SMKs can produce students who understand and can communicate well. Interpersonal communication is sending messages from individuals to other individuals with direct effects and feedback. This research is a research development that aims to develop guidelines to improve interpersonal communication of vocational high school students in entering into the world of work through information services. The sample selection uses purposive sampling. The results of this study indicate a material feasibility test score of 78.9 with a feasible category and expert judgment on the appearance of an appearance with an average score of 85.7 with a very feasible category. As for the practicality test an average score of 92.8 with a high category.